Evaluation of naturally and artificially aged seeds of Phaseolus vulgaris L. - Machado, N. B.; Custodio, C. C.; Takaki, M. [UNESP] (My University, 2001)
Seed ageing is natural phenomenon that occurs in all seeds, including those stored in dry and low temperature rooms. Phaseolus vulgaris L. cv. 'Carioca' seeds harvested in five different years were stored in at 15°C. Seed samples were germinated and evaluated according to The Brazilian Rules for Testing Seeds. The newest seed sample was submitted to artificial ageing. Small (∼1g) samples of all materials (naturally and artificially aged) were ground and proteins extracted. Equal quantities of protein were loaded onto the gels and electrophoresis carried out. Although seeds submitted to 24, 48, 72 and 96 hours of artificial ageing did not show any statistical difference (5%) in relation to unaged seeds in physiological parameters related to emergence, some statistically different parameters related to dry matter and length of shoots and roots occurred. A 24 h of artificial ageing at 41°C improved these factors. Protein patterns were changed after 72 h of artificial ageing and naturally aged seeds showed alterations after two years storage at 15°C. Aged seeds, naturally and artificially, had decreasing germination, vigour, and changes in the characteristic banding pattern of proteins. Physiological parameters and electrophoresis examination showed that for naturally aged seeds physiological parameters were more sensitive while artificially aged seeds, (41°C/100% RH), had electrophoretic profiles that were more efficient for seed lot discrimination.